DEVELOPMENT OF A TRADITIONAL FISHERMEN EMPOWERMENT MODEL THROUGH TECHNOLOGY MODERNIZATION AND INSTITUTIONAL STRENGTHENING IN NORTH LOMBOK - Aryani Rahmawati; Lalu Achmad Tan Tilar Wangsajati Sukmaring Kalih; Hamid Hamid; Luh Gede Sumahiradewi; Sri Agustina; Ilham Ilham (Universitas Mataram, 2025)
Empowering coastal communities is an important strategy for improving the productivity and welfare of traditional fishermen. This study aims to formulate a model for empowering traditional fishermen that integrates technological modernization and institutional strengthening in North Lombok Regency. A Research and Development (R&D) approach was used, with data collected through surveys, interviews, focus group discussions, field observations, and documentation studies. The analysis was conducted descriptively for quantitative data and through data reduction techniques for qualitative data. The results show that modern technology is still rarely used, while fishermen's awareness and interest in adopting it are very high but hampered by capital constraints. On the institutional side, most fishermen are members of groups, but the functions of these organizations are not yet optimal in terms of capital, training, and collective marketing. Based on these findings, the study produced an empowerment model based on three pillars, namely technological modernization, institutional strengthening, and ecosystem support through access to capital, regulations, and multi-stakeholder partnerships. This model is expected to be a realistic and sustainable implementation framework to improve the productivity and welfare of traditional fishermen in the future.